Analysis of Climate Damage Abatement Costs Using a Dynamic Economic Model - Volker Barth; Klaus Hasselmann (Vierteljahrshefte zur Wirtschaftsforschung, 2005)
Future costs arising from climate change and the transformation of the energy system are investigated using a modified version of the Multi-Actor Dynamic Integrated Assessment Model (MADIAM). A cost-benefit analysis is applied to compute optimal business investment scenarios. The economic core of MADIAM describes an economy driven by business striving to maximise profits by investing in physical and human capital. Profits are continually eroded by wage pressures and competition and can be maintained only by investing in human capital (i.e. productivity), which is thus the main driver of economic growth. Future costs accrue from climate damages and the higher expense of non-fossil fuels, which are used either to mitigate climate change or because of declining fossil resources. The impact of various taxation scenarios on the absolute costs, the cost structure and climate change is examined. – – Mit einer modifizierten Version des Multi-Actor Dynamic Integrated Assessment Model (MADIAM) werden die zukünftigen Kosten des Klimawandels und der Transformation des Energiesektors untersucht. Mittels einer Kosten-Nutzen-Analyse werden optimale Investitionsszenarien der Unternehmen berechnet. Im ökonomischen Kernmodell von MADIAM wird die Wirtschaft von der Profitmaximierung der Unternehmen angetrieben, die dazu in physisches und Humankapital investieren. Profite schrumpfen ständig durch Lohndruck und Wettbewerb und können nur durch Investitionen in Humankapital (d.h. Produktivität) auf Dauer erhalten werden. Diese Investitionen sind daher der wesentliche Wachstumsmotor. Zukünftige Kosten entstehen durch Klimaschäden und die höheren Kosten für nichtfossile Energien, die sowohl zur Vermeidung des Klimawandels als auch zum Ausgleich abnehmender fossiler Ressourcen benutzt werden. Wir untersuchen den Einfluss verschiedener Steuerszenarien auf absolute Kosten, auf deren Zusammensetzung und auf die Klimaänderung.
Keywords: 330; Klimawandel; Soziale Kosten; Investitionsentscheidung; Kosten-Nutzen-Analyse; Dynamisches Modell; Umweltökonomik; Theorie